The Relationship Between Anxiety and Masseter Muscle in Temporomandibular Disorders: An Ultrasonographic Assessment - Ocal, Mustafa Cagdas; Baybars, Sumeyye Cosgun; Talu, Merve Hacer (Wiley, 2025)
Objective: This study aimed to investigate the effects of temporomandibular disorders and anxiety on masseter muscle morphology using ultrasonography, considering gender and chewing side preference. Methods: A total of 93 participants, including 67 patients with unilateral disc displacement and 27 healthy controls, were evaluated. Anxiety levels were assessed using the Beck Anxiety Inventory, while temporomandibular disorder severity was determined by the Fonseca Anamnestic Index. Masseter muscle thickness, length, and cross-sectional area were measured bilaterally at rest and during intercuspation using a high-frequency linear probe. Statistical analyses were conducted based on temporomandibular disorder severity, anxiety, gender, and chewing side preference. Results: Participants with disc displacement exhibited significantly increased masseter thickness on the affected side at both rest and intercuspation (p < 0.05), whereas muscle length and cross-sectional area remained unchanged. Individuals with severe anxiety had a significantly greater cross-sectional area compared to those with normal anxiety (p < 0.05), while thickness and length showed no significant differences. Males had significantly greater masseter thickness, length, and cross-sectional area than females (p < 0.05). No significant differences were found concerning chewing side preference (p > 0.05). Conclusion: Temporomandibular disorders and anxiety influence masseter morphology, with variations based on severity and duration. Gender differences were evident, whereas chewing side preference had no significant effect. Ultrasonography proves to be a reliable tool for masseter evaluation, though future studies should incorporate advanced imaging and functional assessments.
Keywords: anxiety; masseter; temporomandibular disorders; ultrasonography